ANALISIS DAYA SAING DAN PENERAPAN STRATEGI DI TK YAA BUNAYYA HIDAYATULLAH KUMAI - Desty Angga Wulan; Siminto (CV. ADIBA ASIHA AMIRA, 2023)
Kindergarten which is a level of education prior to basic education must formulate strengths, weaknesses, opportunities and threats and have a SWOT strategy in order to compete with other schools in a healthy manner. This type of research is classified as qualitative and quantitative research. Data were collected through questionnaires, observations, and interviews. The method of data analysis is the analysis of internal and external factors, IFAS, EFAS and SWOT matrices. In conclusion, based on the SWOT analysis, according to the Cartesian diagram, Yaa Bunayya Kindergarten is located in Quadrant I, namely internal factors with a score of (1.95) and external factors with a score of (1.37). Yaa Bunayya Kindergarten's SO strategy includes continuing to motivate and explore to add quality learning in order to maintain the school's A accreditation, more intensive promotions to stakeholders so that they want to become regular donors and have more trust in stakeholders so that they want to become regular donors and have more trust in this school , Make the funds provided by sponsors as support to increase development in schools such as mosques and libraries. Locations that are far from cities should make teachers more solid with good communication, Maintain good relations with other schools and accept suggestions and criticism if there are deficiencies. Yaa Bunayya Kindergarten's WO strategy includes adding new tahfidz teachers, reviving committee funds to fill the school's unique vacancies, implementing outdoor learning so that learning is varied and opening children's insights about nature, holding training, training and teacher work groups to improve quality and teacher performance as educators. Use BOP funds to buy, equip and fund schools to add school equipment and games. ST TK Yaa Bunayya's strategy includes improving communication with stakeholders, submitting a funding proposal to the regent to repair roads, improving services with stakeholders, changing the tahfidz schedule which previously could be 3x a week and adjusting the schedule to the condition of the teacher, providing evidence and attachments to financial documents that relevant for submitting funds to foundations. Yaa Bunayya's WT TK strategy includes increasing promotion and outreach to the community around the kindergarten, increasing government relations to make it easier to apply for funds to local governments, increasing stakeholders and promotions can be carried out outside the school district, holding scholarships for undergraduate education schools, applying for funds to foundations done remotely. Far in advance so that the proposed financing is not too late.